First-principles microkinetic study of methane and hydrogen sulfide catalytic conversion to methanethiol/dimethyl sulfide on Mo6S8 clusters: activity/selectivity of different promoters. Issue 17 (1st August 2019) - Arvidsson, Adam A.; Taifan, William; Hellman, Anders; Baltrusaitis, Jonas
Abstract : A large fraction of the global natural gas reserves is in the form of sour gas, i.e. contains hydrogen sulfide (H2 S) and carbon dioxide (CO2 ), and needs to be sweetened before utilization. Abstract : A large fraction of the global natural gas reserves is in the form of sour gas, i.e. contains hydrogen sulfide (H2 S) and carbon dioxide (CO2 ), and needs to be sweetened before utilization. The traditional amine-based separation process is energy-intensive, thereby lowering the value of the sour gas. Thus, there is a need to find alternative processes to remove, e.g., hydrogen sulfide. Mo6 S8 clusters are promising candidates for transforming methane (CH4 ) and hydrogen sulfide into methanethiol (CH3 SH) and dimethyl sulfide (CH3 SCH3 ), which are high-value sulfur-containing products that can be further used in the chemical industry. Here first-principles microkinetics is used to investigate the activity and selectivity of bare and promoted (K, Ni, Cl) Mo6 S8 . The results show that methanethiol is produced via two different pathways (direct and stepwise), while dimethyl sulfide is formed via a competing pathway in the stepwise formation of methanethiol. Moreover, there is an increase in activity and a decrease in selectivity when adding an electropositive promoter (K), whereas the reverse behaviour is observed when adding an electronegative promoter (Cl). When adding Ni there is also a decrease in activity and an increase in selectivity; however, Ni is acting as an electron donor. The results provide insights and guidance as to what catalyst formulation is preferred for the removal of hydrogen sulfide in sour gas.